2013
DOI: 10.12777/ijse.4.2.61-65
|View full text |Cite
|
Sign up to set email alerts
|

Physical Characteristics of Pressed Complete Feed for Dairy Cattle

Abstract: The study was aimed to evaluate the physical characteristics of the pressed complete feed in the forms of cube, cylinder and ball. The study was conducted to get a complete feed of dairy cows that can be developed commercially. The evaluation was done on a physical test : bulkiness, hardness and hygroscopic properties of pressed complete feeds. The results of this research showed that the bulkiness of pressed complete feed in the forms cubes, cylinders and balls were between 0.20 up to 0.48 liter/kg; the hardn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(5 reference statements)
1
2
0
Order By: Relevance
“…94 to 99% as the time after mixing the components increased from 30 min to 1 hr on both urea and straw-based feed blocks, respectively. Authors in [7] and [8] reported similar results for completed-feed blocks prepared for dairy animals. The durability of wheat and rice straw-based whole feed blocks ranged between 70.52 and 78.83%, according to [9], with rice straw-based blocks having significantly greater durability.…”
Section: ░ 4 Results and Discussionsupporting
confidence: 53%
“…94 to 99% as the time after mixing the components increased from 30 min to 1 hr on both urea and straw-based feed blocks, respectively. Authors in [7] and [8] reported similar results for completed-feed blocks prepared for dairy animals. The durability of wheat and rice straw-based whole feed blocks ranged between 70.52 and 78.83%, according to [9], with rice straw-based blocks having significantly greater durability.…”
Section: ░ 4 Results and Discussionsupporting
confidence: 53%
“…The hardness of the feed cube is 12.5 lbs and the cylinder is 9.66 lbs. Hygroscopic feed cube 3.3% and cylinder 2.41% (Munasik et al, 2013).…”
Section: Physical Quality Of Compacted Feedmentioning
confidence: 99%
“…Feed blocks are used to deliver real estate and medicines in specified rates, facilitate their handling, have an effective role in the agricultural field, and manufacture animal feed, and also greatly facilitate the process of transportation, storage and presentation in the containers. (Munasik et al, 2013). Manufactured feed blocks are easy to transport and handle.…”
Section: Introductionmentioning
confidence: 99%